Change in the perceived certainty of punishment as an inhibitor of post-juvenile offending in serious delinquents: deterrence at the adult transition - Walters, Glenn D. (Crime & delinquency, 2018)
The purpose of this study was to determine whether growth in perceived certainty of punishment explained the right leg of the age–crime curve. Using longitudinal data from the Pathways to Desistance study (N = 1,354), it was determined that offense variety achieved its steepest decline between the ages of 17 and 18, and offense frequency displayed its steepest decline between the ages of 19 and 20. Further analysis revealed that perceived certainty of punishment predicted the variety and frequency of offending from the periods of steepest decline but not during periods of offense growth or less optimal decline. These results provide preliminary support for the presence of sensitive periods in emerging adulthood whereby increased perceived certainty may inhibit future offending.